2019
DOI: 10.1097/ico.0000000000001971
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Corneal Biomechanics in Chinese Preschool Children With Different Refractive Status

Abstract: Purpose: To investigate the characteristics of corneal biomechanics in Chinese preschool children with different refractive status. Methods: Study participants were 108 Chinese children (216 eyes) aged 4 to 6 years with a spherical equivalent refraction between −9.00 and +9.00 diopters (D). Cycloplegic refraction was measured using an autorefractor, axial length using an IOL Master (Zeiss, Oberkochen, Germany), and corneal biomechanical metrics and corn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 22 publications
5
25
0
Order By: Relevance
“…Especially the cornea in high myopia had faster outward corneal velocity (OCV) and higher CDA compared to emmetropia [ 16 ]. Long found in Chinese children, SP - A1 declined gradually between presbyopia, emmetropia and myopia groups [ 38 ]. However, in Lim’s study, CH and CRF were not significantly correlated with refractive errors by ORA measurement in corneal biomechanics in children aged 7–9 years.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the cornea in high myopia had faster outward corneal velocity (OCV) and higher CDA compared to emmetropia [ 16 ]. Long found in Chinese children, SP - A1 declined gradually between presbyopia, emmetropia and myopia groups [ 38 ]. However, in Lim’s study, CH and CRF were not significantly correlated with refractive errors by ORA measurement in corneal biomechanics in children aged 7–9 years.…”
Section: Discussionmentioning
confidence: 99%
“…The higher the degree or the longer the AL of the myopic eye, the less time is needed to return to the origin after applanation, as its viscoelasticity increased. In a recent study [ 27 ], myopia had greater A2-velocity indicating that the cornea tends to be more deformable and softer than emmetropia and hyperopia in children. Therefore, A2-velocity may be another indicator of corneal elasticity, as Lee et al [ 12 ], Miki et al [ 24 ] and Wang et al [ 28 ] suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Especially the cornea in high myopia had worse biomechanics compared to emmetropia 15 . Long found in Chinese children, SP -A1 declined gradually between presbyopia, emmetropia and myopia group 33 . However, in Lim's study, CH and CRF were not signi cantly correlated with refractive errors by ORA measurement in corneal biomechanics in children aged 7-9 years.…”
Section: Resultsmentioning
confidence: 89%